(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2019)
In vivo dosimetry is an essential tool for quality assurance programs, being a procedure commonly performed with thermoluminescent dosimeters (TLDs) or diodes. However, a type of dosimeter that has increasing popularity in recent years is the metal-oxide-semiconductor field effect transistor (MOSFET) detector. MOSFET dosimeters fulfill all the necessary characteristics to realize in vivo dosimetry since it has a small size, good precision and feasibility of meas-urement, as well as easy handling. Nevertheless, its true differential is to allow reading of dose in real time, enabling immediate intervention in the correction of physical parameters deviations and anticipation of small anatomical changes in the patient during treatment. In order for MOSFET dosimeter to be better accepted in clinical routine, information reporting performance should be available frequently. For this reason, this work proposes to verify reproducibility and angular dependence of a standard sensitivity MOSFET dosimeter (TN-502RD-H) for Cs-137 and Co-60 sources. Exper-imental data were satisfactory and MOSFET dosimeter presented a reproducibility of 3.3% and 2.7% (±1 SD) for Cs-137 and Co-60 sources, respectively. In addition, an angular dependence of up to 6.1% and 16.3% for both radioactive sources, respectively. It is conclusive that MOSFET dosimeter TN-502RD-H has satisfactory reproducibility and a considerable angular dependence, mainly for the Co-60 source. This means that although precise measurements, special attention must be taken for applications in certain anatomical regions in a patient.